The making and unmaking of whiteness - Brander Rasmussen, Birgit 1968-; Klinenberg, Eric 1970-; Nexica, Irene J.; Wray, Matt 1964- (Duke University Press, 2012)
Universal freckle, or how I learned to be white / Dalton Conley -- "The souls of white folks" / Mab Segrest -- The mirage of an unmarked whiteness / Ruth Frankenberg -- White racial projects / Howard Winant -- The "Morphing" properties of whiteness / Troy Duster -- "White devils" talk back : what antiracists can learn from whites in Detroit / John Hartigan Jr. -- Transnational configurations of desire : the nation and its white closets / Jasbir Kaur Puar -- Perfidious Albion : whiteness and the international imagination / Vron Ware -- The new liberalism in America : identity politics in the "vital center" / Eric Lott -- How gay stays white and what kind of white it stays / Allan Bérubé -- (E)racism : emerging practices of antiracist organizations / Michael Omi -- Moving from guilt to action : antiracist organizing and the concept of "whiteness" for activism and the academy / William Aal